Atomic resolution imaging of the edges of catalytically etched suspended few-layer graphene. - Schäffel, F; Wilson, M; Bachmatiuk, A; Rümmeli, M; Queitsch, U; Rellinghaus, B; Briggs, G; Warner, J (2011)
Nanostructured graphene and graphene nanoribbons have been fabricated by catalytic hydrogenation, and the edge smoothness has been examined via direct imaging with atomic resolution. When abstaining from solvents during sample preparation, the prepared nanoribbons possess clean edges ready for inspection via transmission electron microscopy (TEM). Edges with subnanometer smoothness could be observed. A method has been developed to make catalytic hydrogenation experiments compatible with TEM, which enables monitoring of the nanoparticles prior to and after hydrogenation. In this way, etching of free-standing few-layer graphene could be demonstrated. Our results enable evaluation of the degree of edge control that can be achieved by means of catalytic hydrogenation.